Metabolic engineering of oilseed crops to produce high levels of novel acetyl glyceride oils with reduced viscosity, freezing point and calorific value. Issue 6 (10th March 2015) - Liu, Jinjie; Rice, Adam; McGlew, Kathleen; Shaw, Vincent; Park, Hyunwoo; Clemente, Tom; Pollard, Mike; Ohlrogge, John; Durrett, Timothy P.
Summary Seed oils have proved recalcitrant to modification for the production of industrially useful lipids. Here, we demonstrate the successful metabolic engineering and subsequent field production of an oilseed crop with the highest accumulation of unusual oil achieved so far in transgenic plants. Previously, expression of the Euonymus alatus diacylglycerol acetyltransferase (EaDAcT) gene in wild‐type Arabidopsis seeds resulted in the accumulation of 45 mol% of unusual 3‐acetyl‐1, 2‐diacyl‐sn‐glycerols (acetyl‐TAGs) in the seed oil (Durrett et al., 2010 PNAS 107:9464). Expression of EaDAcT in dgat1 mutants compromised in their ability to synthesize regular triacylglycerols increased acetyl‐TAGs to 65 mol%. Camelina and soybean transformed with the EaDAcT gene accumulate acetyl‐triacylglycerols (acetyl‐TAGs) at up to 70 mol% of seed oil. A similar strategy of coexpression of EaDAcT together with RNAi suppression of DGAT1 increased acetyl‐TAG levels to up to 85 mol% in field‐grown transgenic Camelina. Additionally, total moles of triacylglycerol (TAG) per seed increased 20%. Analysis of the acetyl‐TAG fraction revealed a twofold reduction in very long chain fatty acids (VLCFA), consistent with their displacement from the sn‐3 position by acetate. Seed germination remained high, and seedlings were able to metabolize the stored acetyl‐TAGs as rapidly as regular triacylglycerols. Viscosity, freezing point and caloric content of the Camelina acetyl‐TAG oils were reduced, enabling use of this oil in several nonfood and food applications.